2011
DOI: 10.1002/hep.24628
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in interferon signaling define natural killer cell response and refractoriness to interferon-based therapy of hepatitis C patients

Abstract: Natural killer (NK) cells exhibit a polarized phenotype with increased cytotoxicity and decreased IFN- γ production in chronic hepatitis C virus (HCV) infection. Here we asked whether this is due to type I interferon (IFN)-induced expression and phosphorylation levels of signal transducer and activator of transcription (STAT) molecules in NK cells and whether it affects the response and refractoriness of NK cells to IFN-α-based therapy of hepatitis C. STAT1 levels in NK cells were significantly higher in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 23 publications
10
100
0
Order By: Relevance
“…Taken together, these findings indicate that STAT1 induction is impaired in chronically infected VLϩ hepatitis C subjects and suggest a critical role for STAT1 in clearance of HCV. This is consistent with observations of monocytes and NK cells from chronically infected hepatitis C patients, in which levels of phosphorylated STAT1 correlated inversely with levels of programmed cell death 1 (PD-1) expression and better response to IFN therapy, respectively (28,29).…”
Section: ϫ6supporting
confidence: 91%
“…Taken together, these findings indicate that STAT1 induction is impaired in chronically infected VLϩ hepatitis C subjects and suggest a critical role for STAT1 in clearance of HCV. This is consistent with observations of monocytes and NK cells from chronically infected hepatitis C patients, in which levels of phosphorylated STAT1 correlated inversely with levels of programmed cell death 1 (PD-1) expression and better response to IFN therapy, respectively (28,29).…”
Section: ϫ6supporting
confidence: 91%
“…Progression of HIV infection has also been linked to both type I IFN (12) and expression of particular NK cell receptors (13). Similarly, the activation state of NK cells and type I IFN have been linked to both chronicity of HCV infection and refractoriness to antiviral therapy (14,15). Recently, two groups demonstrated that blockade of type I IFN signaling during persistent LCMV infection in mice could facilitate viral clearance (16,17).…”
Section: Persistent Virus Infections Are a Major Threat To Global Hummentioning
confidence: 99%
“…HCV also enhances the susceptibility of primary human hepatocytes to TRAIL-mediated killing via increased expression of the death receptors DR4 and DR5 (81). The ex vivo expression of TRAIL and CD107a on NK cells increases as early as hours following the initiation of antiviral therapy (82,83), correlates with the induction of phosphorylated STAT1 levels (84), and is associated with early virologic response. Thus, on aggregate, these data identify NK cell markers associated with protection from early infection and predictors of response to IFN-based therapy.…”
Section: Figurementioning
confidence: 99%